2019
DOI: 10.1088/1674-1056/28/5/055201
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline order and disorder in dusty plasmas investigated by nonequilibrium molecular dynamics simulations*

Abstract: The particle structure of a complex system has been explored through a unique Evans's homogenous nonequilibrium molecular dynamics (HNEMD) simulation technique. The crystalline order–disorder structures (OD-structures) and the corresponding energies of three-dimensional (3D) nonideal complex systems (NICSs) have been measured over a wide range of plasma states (Γ, κ) for a body-centered cubic (BCC) structure. The projected technique provides accurate OD-structures with fast convergence and applicable to very s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…In this work, the effect of crystal orientations and loading conditions on the deformation behaviors of HCP-Ti is investigated using MD simulations, which has been used widely to explain the mechanical behavior and detailed deformation process of materials. [23][24][25][26][27][28] The results show that the deformation behavior strongly depends on orientation and loading mode. This work will provide a new sight in the orientation-dominated plastic deformation mechanism.…”
Section: Introductionmentioning
confidence: 96%
“…In this work, the effect of crystal orientations and loading conditions on the deformation behaviors of HCP-Ti is investigated using MD simulations, which has been used widely to explain the mechanical behavior and detailed deformation process of materials. [23][24][25][26][27][28] The results show that the deformation behavior strongly depends on orientation and loading mode. This work will provide a new sight in the orientation-dominated plastic deformation mechanism.…”
Section: Introductionmentioning
confidence: 96%
“…The magnetization of charged particles can greatly change the Bohm criterion at the sheath edge and electron dynamics among the sheath region, which then influences the sheath potential profile and other properties. Many authors have used molecular dynamics and fluid simulations to study the characteristics of complex plasmas [14][15][16][17][18][19]. In former studies, electrons are considered to follow the Maxwellian distribution, but recently many studies have shown that electrons in the sheath region could vary from the Maxwellian distribution [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the structural properties of nanomaterials is a crucial aspect of nanotechnology having a wide range of potential applications [1]. Over the past two decades, significant progress has been made in this field through the utilization of experimental, theoretical, and computational methodologies.…”
Section: Introductionmentioning
confidence: 99%